Amanita annulata, a new species of Amanita section Vaginatae with an annulus from southwestern China - Zhang, Wen-Hao; Huang, Ting; Huang, Hong-Yan; Tang, Li-Ping (Phytotaxa, 2021)
A species with an annulus is rare within Amanita section Vaginatae. In this study, A. annulata is proposed as a new species based on morphological and molecular evidence. It is the second annulate species of the section in China, the first being A. cingulata. The new species is found in forests dominated by Fagaceae in Yunnan Province of China. It is characterized by its large basidioma, white pileus covered with large, white, dingy yellow-tipped pyramidal warts that break off easily, a stipe with a mealy, evanescent, white annulus, the base of the stipe covered with concolorous pyramidal warts, and broadly ellipsoid to ellipsoid basidiospores measuring 11−15 × 9−12 μm. Moreover, it is compared with similar species, especially the annulate taxa of Amanita section Vaginatae.